Street in Dawson (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1898)
1 Lantern Slide: b&w; 10 x 8 cm. Reproduction photo of Dawson street scene. Reproduction photograph acquired by Mart Albert Howard for instructional/educational purposes.